Creationist Conceptions in 14 Countries. How to Teach Evolution to French Students Coming from Immigration? - (:unkn) unknown (My University, 2009)
Even in France, where creationist ideas are not widespread, more and more teachers are confronted to some difficulties when teaching the biological evolution, mainly with students coming from families immigrated from North Africa or Sub-Saharan Africa. In a first part, to better realize the conflict between the French culture and their African initial culture, we will present some results analyzing the creationist ideas of teachers in 14 countries (n = 5706), including France and 5 African countries (Morocco, Algeria, Tunisia, Senegal and Burkina Faso). We will then analyze the creationist conceptions of 17-18 year old students in a high school of the suburb of Lyon (France) and the main epistemological and socio-cultural obstacles to learning evolution. We will finally present the new strategies of two teachers (biology and philosophy) to help their students to accept the idea that biological evolution is not in contradiction with their possible belief in God, science and religion being two distinct areas.
Keywords: African Research